Analysis of Environmental, Social and Economic Conditions in the Ecosystem Restoration Area (Case Study in IUPHHK-RE PT. Sinar Mutiara Nusantara, Pelalawan Regency) - Fathoni Ahmad; Ridwan Manda Putra; Zulkarnain Umar (Berkala Perikanan Terubuk, 2023)
The problems that are often encountered in ecosystem restoration activities today are no longer just technical forestry issues such as planting and maintenance, but more importantly social issues as an important part of ecosystem restoration area management. Forest management must change from a physical definition to social interactions and spatial patterns so that the solutions taken must seek contextual efforts according to field conditions. Given the huge potential of the Kampar Peninsula ecosystem restoration area by PT. Sinar Mutiara Nusantara, it is necessary to carry out an in-depth analysis of environmental, social and economic conditions. The purpose of this study was to analyze the environmental, social and economic conditions of the Kampar Peninsula ecosystem restoration area by PT. Sinar Mutiara Nusantara. The environmental conditions observed consisted of land cover change data, vegetation and fauna data as well as mammals. While socio-economic data were obtained directly by observation (direct observation) and in-depth interviews with the people living around the concession and interacting with the IUPHHK-RE area of PT. Sinar Mutiara Nusantara in Pelalawan Regency. The results showed that the Kampar Peninsula ecosystem restoration area by PT. Sinar Mutiara Nusantara has high natural resources, as evidenced by the changing conditions of land cover, the potential for diverse vegetation and fauna and mammals. Not only environmental conditions, but socio-economic conditions which are also very closely related to environmental conditions in the Kampar Peninsula ecosystem restoration area by PT. The Best One United.